2020
DOI: 10.1136/heartjnl-2019-316067
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, risk factors and outcome of young patients with myocardial infarction

Abstract: ObjectiveThe decline in the incidence and mortality of acute myocardial infarction (AMI) has been less among younger compared with older individuals. The aim of this nationwide study was to assess the current incidence, risk factors and outcome of AMI in patients <45 years of age.MethodsAll patients ≤80 years of age registered in the Norwegian Myocardial Infarction Register in 2013–2016 were included in this observational, nationwide cohort study. Follow-up was conducted through linkage with the Norwegian P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
65
1
29

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(100 citation statements)
references
References 26 publications
5
65
1
29
Order By: Relevance
“…The relationship between dyslipidemia and vascular risk is well‐recognized. It has been determined that patients <45 years with cardiovascular events have higher low‐density lipoprotein cholesterol (LDL‐C) than the respective group of patients >45 years (45–80 years) 17 . Additionally, vascular events in this age group (<45 years) have been linked to only mildly abnormal values of total cholesterol (TC), LDL‐C, high‐density lipoprotein cholesterol (HDL‐C), and triglycerides (TGs) in statin‐naïve adults 18 .…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between dyslipidemia and vascular risk is well‐recognized. It has been determined that patients <45 years with cardiovascular events have higher low‐density lipoprotein cholesterol (LDL‐C) than the respective group of patients >45 years (45–80 years) 17 . Additionally, vascular events in this age group (<45 years) have been linked to only mildly abnormal values of total cholesterol (TC), LDL‐C, high‐density lipoprotein cholesterol (HDL‐C), and triglycerides (TGs) in statin‐naïve adults 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Several traditional risk factors for coronary artery disease (CAD), which include current smoking status, elevated body mass index (BMI), and a family history of premature acute myocardial infarction (AMI), have been associated with younger age [3]. In addition, non-traditional risk factors, such as hyperhomocysteinemia (HHCY), have also been suggested as novel markers for CAD and are supposed to be added to Framingham Risk Factors (FRFs) to boost their predictive value [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…In studies accepting the age limit as <40-45, the incidence of acute MI has been reported to be between 4-10%. 2,17 ın our study, among all patients who had acute STEMI 5.65% were in the age group of ≤ 40 years. Since the first definition of acute MI, different inclusion criteria have been used in different geographies and different populations, especially in the last 10 years.…”
Section: Discussionmentioning
confidence: 64%
“… 1 Although acute ST-segment elevation myocardial infarction (STEMI) is mainly seen in the elderly, 4-10% of patients with acute STEMI have been reported to be under the age of 45. 2 , 3 The incidence of STEMI in young individuals has been reported to be between 2-12% in different studies. This wide range of incidences depends on the use of different cut-off values ​​ranging from the age of 35-55 for the definition of ‘young’ in the studies.…”
Section: Introductionmentioning
confidence: 99%